How to gather? : Acting in a center in a city in the heart of the island of Eurasia. - Moscow Biennale of Contemporary Art Moscow 2015; Ayas, Defne; Backstein, Joseph; De Baere, Bart; Schafhausen, Nicolaus; The, Unbound (Moscow : Institute of Contemporary Art, 2015)
Koolhaas, Rem ; Brey, Ricardo ; Bratkov, Sergey ; Hyber, Fabrice ; Maes, Ives ; d'o, Honoré ; Tuymans, Luc ; Afif, Saâdane ; Colson, Vaast ; Kahane, Leon ; Kuzkin, Andrey ; et al.
6th Moscow Biennale of Contemporary Art, Moscow, September 22 - October 1, 2015
kunstcatalogus